2006
DOI: 10.1001/jama.296.13.1593
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sudden Cardiovascular Death in Young Competitive Athletes After Implementation of a Preparticipation Screening Program

Abstract: The incidence of sudden cardiovascular death in young competitive athletes has substantially declined in the Veneto region of Italy since the introduction of a nationwide systematic screening. Mortality reduction was predominantly due to a lower incidence of sudden death from cardiomyopathies that paralleled the increasing identification of athletes with cardiomyopathies at preparticipation screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,075
4
72

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,335 publications
(1,177 citation statements)
references
References 43 publications
26
1,075
4
72
Order By: Relevance
“…However, it is possible that exercise may be proarrhythmic not only because of its link with adrenergic surge, but also via electrophysiologic remodeling. Countries that implemented preparticipation screening had shown dramatic reduction of ACM‐related deaths in athletes 12. The current study of Wang and colleagues10 offers data suggesting that the electrophysiologic changes that strenuous exercise determine could be at least partially reversed by removing the “stressor” (ie, intense physical activity).…”
Section: Introductionmentioning
confidence: 74%
“…However, it is possible that exercise may be proarrhythmic not only because of its link with adrenergic surge, but also via electrophysiologic remodeling. Countries that implemented preparticipation screening had shown dramatic reduction of ACM‐related deaths in athletes 12. The current study of Wang and colleagues10 offers data suggesting that the electrophysiologic changes that strenuous exercise determine could be at least partially reversed by removing the “stressor” (ie, intense physical activity).…”
Section: Introductionmentioning
confidence: 74%
“…3,38 The American Heart Association, unlike the European Society of Cardiology and the International Olympic Committee, has for the time being chosen not to endorse pre-participation ECG screening, in part due to concerns about potentially high costs associated with universal implementation within the U.S. 38 Regardless of any formalized recommendations for or against such pre-participation screening, the improved specificity of A-ECG scoring, if corroborated in future prospective studies, might aid in reducing those costs that are now incurred when truly unnecessary further testing occurs based on strictly conventional ECG analysis. Additionally, because of improved sensitivity, A-ECG scoring with full-disclosure ECG might also be preferred over isolated conventional ECG for initial screening of higher-risk individuals, such as those with syncope or family histories of HCM.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the U.S., HCM accounts for more than one-third of fatal cardiac arrests in young competitive athletes. 3 Early identification of patients with HCM is essential due to the high risk of SCD in this population. To this end, 12-lead ECG has been suggested as an inexpensive and useful screening tool, one that in certain situations may be more sensitive than echocardiogram.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing physical activity leads to increased heart rate, myocardial stress, and oxygen demand, predisposing patients to recurrent arrhythmias [16,35,3941]. BBs blunt these effects; however, no current clinical trial showed definitive mortality benefit for BB in patients with ARVC.…”
Section: Beta-blockersmentioning
confidence: 99%